Graphene-Based Composite Membrane Prepared from Solid Carbon Source Catalyzed by Ni Nanoparticles - Jing Li; Jialiang Liu; Jinshui Liu; Jinfeng Lai; Yuxun Chen; Wenjun Li (Nanomaterials, 2021)
Emerging as a light, flexible and highly thermally conductive material, graphene-based membranes have attracted extensive attention in thermal management field. However, the preparation of high-quality graphene-based membranes usually involves complex processes and thermal annealing at ultra-high temperature, which limits their large-scale application in thermal management field. In our study, reduced graphene oxide-Ni-hydroxypropyl methyl cellulose (RGO-Ni-HPMC) composite membrane was prepared from catalytic pyrolysis of hydroxypropyl methyl cellulose (HPMC) with Ni nanoparticles to generate multilayer graphene and form phonon transport channels between adjacent graphene layers. Further, our study shows that the RGO-Ni-HPMC composite membrane has a good heat dissipation effect at the hot spots at high temperature. The average temperature of hot spots is reduced by 11.5 °C. It is expected to solve the heat dissipation problem of high-power electronic equipment.